Safety of Palivizumab Stewardship in Conjunction with Infection Prevention and Control Strategies for Healthcare-Associated Respiratory Syncytial Virus Infections. (21st February 2018) - Patel, Rupal M.; Kociolek, Larry K.; Merrick, Emily; Reuter, Caroline; Kronforst, Kenny; Zheng, Xiaotian; Patel, Sameer J.
ABSTRACT: Transitioning from administration of monthly palivizumab to a single dose at discharge was associated with substantial pharmacy cost savings. With the concurrent adoption of private hospital rooms and visitor restriction policies, hospital-wide and neonatal intensive care unit healthcare-associated respiratory syncytial virus infections decreased following these changes. Infect Control Hosp Epidemiol 2018;39:485–487